International practices of organizing emergency medical care for foreign citizens - G. D. Petrova; V. A. Afanasyev; O. I. Bezzubenko (Здоровье мегаполиса)
The article discusses the international practices of organizing emergency care for foreigners when specialized assistance companies directly coordinate the process. The involvement of the national health care system in the provision of emergency and acute care to non-residents directly shapes the global reputation of the country as a healthcare and tourist destination. This reflects the objectives laid down by the Government of the Russian Federation in the national project policies.Purpose: to study the role of specialized medical assistance companies in the Russian health care system for foreigners, to identify aspects of their work and evaluate their potential contribution to shaping and developing global reputation of the Russian healthcare system.Results and conclusion. Study shows that today assistance companies are an underestimated participant on the Russian medical tourism market that could help strengthen the regional and federal healthcare destinations and provide new opportunities for Russian medical organizations. Few Russian studies have investigated impact of assistance companies, which in turn limits the tools for raising tourist attractiveness of the Russian Federation and its constituent entities.